NPR Šúr – významná lokalita vodních měkkýšů - Luboš Beran (Malacologica Bohemoslovaca, 2023)
The Šúr National Nature Reserve is one of the most significant wetlands in Central Europe, featuring an extensive area of alder carrs. In 2023, a study was conducted on the aquatic molluscs within this reserve. In total, 20 species of aquatic molluscs (17 gastropods and 3 bivalves) were found across 11 sites. Most species thrive in overgrown shallow to periodic habitats, which aligns with the characteristics of the predominant habitats formed by alder carrs and reeds. The rare and relict gastropod Valvata macrostoma has been verified at Šúr NNR. The population of Ladislavella occulta was found, constituting the second known site of this species in Slovakia. These research findings are following previous survey results.